Pengembangan Asesmen Hots Multiple Choice Mengunakan Aplikasi Quizizz Di Sekolah Dasar - Dicky Dermawan, Deden; Arrahim (Jurnal Elementaria Edukasia, 2023)
Research on developing assessments based on Higher Order Thinking Skills (HOTS) with the help of the quizizz application during learning from home by utilizing features in online applications in the learning process. This study aims to produce a Higher Order Thinking Skill (HOTS) based assessment for fifth grade elementary schools in science learning theme 8 The environment of our friend that is valid, reliable, feasible, and practical. This research method uses R&D research with the ADDIE research design (analysis, design, development, implementation, and evaluation). The steps developed include design, expert validation, limited scale trials, and large scale trials. The assessment developed is a multiple choice question using the quizizz application. Data collection techniques in this development research using test techniques (multiple choice) and practicality questionnaires. The results of the HOTS-based multiple choice assessment validation are valid, the reliability value when the limited scale trial is 0.648 and when the large scale trial is 0.762 the value indicates the assessment is reliable. revisions", namely 15 item items, the criterion "Acceptable without revision", namely 7 item items, the criteria with "Good" questions, namely 8 item items and the broad scale shows the different power of the 30 questions, there is the criterion "Acceptable with revisions", namely 15 item items, the criterion "Acceptable without revision" is 7 item questions, the criteria with the question "Good" is 8 item questions. Analysis of the difficulty level of the limited scale test items, 7 questions with Easy criteria, 20 questions with Medium criteria, and 3 questions with Difficult criteria and on a wide scale it shows 12 questions with Easy criteria, 16 questions with Medium criteria, and 2 questions with Difficult criteria . The practicality questionnaire uses 4 raters which show very practical criteria.